Hubungan Pendidikan Dan Usia Ibu Dengan Pengetahuan Ibu Tentang Pesan-Pesan Gizi (Pemberian Mp-Asi) Di Buku Kia Di Desa Bulusulur Kabupaten Wonogiri - REJEKI, SRI (2012)
Background : Maternal and child health programs provide maternal and child health books (MCH) which contains records of maternal health and child as well as a variety of information how to maintain Maternal and child health. Factors that affect a person's knowledge is education, experience and age. The results of the data collection in the health center I Wonogiri in 2011 showed that babies be breastfed exclusively for 42.93% and 57.37% likely to be given formula milk and food additives, while the data obtained by investigators about formula feeding and food additives are the highest in the region Winton Health Center I was working at the Village Bulusulur 52.33% as of 86 infants. Purpose : Determine the relationship of education and maternal age with maternal knowledge about nutrition messages (giving MP-ASI) MCH on books in the village bulusulur wonogiri district. Research Methods : This study is an observanal study using cross sectional approach The number of respondents as many as 52 people. Data characteristics of respondents, maternal education, maternal age and maternal knowledge obtained by questionnaire. Uji statistik untuk mengetahui hubungan diantara variabel menggunakan korelasi Rank Spearman. Results : Most mothers have secondary education is high school graduation as much as 53.84%. Most adult age category (21-40 years) of 88.46% or 46 people. A total of 42.3% had no knowledge of good and has a good knowledge of as much as 57.7%. It is recommended nutrition program manager can provide information about the provision of complementary feeding and introduce the importance of books KIA cadres and mother to mother under two years. Conclusion: There was no significant association with maternal education and age of maternal knowledge about nutrition messages (giving MP-ASI) in MCH at Village Books Bulusulur Wonogiri.